1999
DOI: 10.1046/j.1365-2958.1999.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

A ketolide resistance mutation in domain II of 23S rRNA reveals the proximity of hairpin 35 to the peptidyl transferase centre

Abstract: Ketolides represent a new generation of macrolide antibiotics. In order to identify the ketolide-binding site on the ribosome, a library of Escherichia coli clones, transformed with a plasmid carrying randomly mutagenized rRNA operon, was screened for mutants exhibiting resistance to the ketolide HMR3647. Sequencing of the plasmid isolated from one of the resistant clones and fragment exchange demonstrated that a single U754A mutation in hairpin 35 of domain II of the E. coli 23S rRNA was sufficient to confer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
131
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 35 publications
(59 reference statements)
11
131
1
3
Order By: Relevance
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Various ketolides differ from CEM-101 in the chemical nature of the alkyl-aryl side chain and the site of its attachment to the lactone scaffold. Nevertheless, in the RNA probing experiments, all these drugs afford a nearly complete protection of A752 in the E. coli ribosome from chemical modification (9,17,48,49), indicating that the interaction of the alkyl-aryl side chain with the A752-U2609 base pair is important for binding of a range of clinically relevant ketolides to the ribosome. Despite a generally similar orientation of the side chains of CEM-101 and telithromycin, the variation in their chemical structures produces an important difference in the mode of binding.…”
Section: Vol 54 2010 Interaction Of a New Fluoroketolide With The Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these compounds inhibit cell growth by interfering with peptide bond formation (15). The second major antibiotic binding site in the large ribosomal subunit is located at the upper segment of the nascent peptide exit tunnel (NPET), adjacent to the PTC, and is used by macrolides and type B streptogramins (3,7,(16)(17)(18)(19)(20)(21). Binding to this site impedes progression of the nascent proteins toward the tunnel exit.…”
mentioning
confidence: 99%
“…7 Their mechanism of action has been reported to interact with nucleotide A752 directly in domain II of the 23S rRNA in addition to the main interaction of the drugs in domain V and inhibit protein synthesis by blocking elongation. 8 This results in tighter binding to ribosomes and imparts some activity against methylated ribosomes in some species. 9,10 The study of the high-resolution X-ray co-crystal structures has revealed that macrolides bind at the entrance to the peptide tunnel in the 23S rRNA, and the cladinose group in their structures is located at and fits with the cavity formed by G2505, C2610 and C2611 in domain V. 11 On the basis of the results of the X-ray co-crystal structure study, many new derivatives of macrolides for the effective management of erythromycin resistance have been investigated by different research groups.…”
Section: Introductionmentioning
confidence: 99%